RESEÑA de : Azcárate Luxán, B.; Azcárate Luxán, M.A.; Sánchez Sánchez, J. Atlas histórico y geográfico universitario. Madrid : UNED, 2006 - Andreu Pintado, Javier (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2005)
-